Design of radiation-hardened memory cell by polar design for space applications. (February 2023) - Hao, Licai; Liu, Li; Shi, Qi; Qiang, Bin; Li, Zhengya; Liu, Nianlong; Dai, Chenghu; Zhao, Qiang; Peng, Chunyu; Lu, Wenjuan; Lin, Zhiting; Wu, Xiulong
Abstract: This paper proposed a radiation-hardened memory cell (RHMC12T) by polar design for space applications. The proposed cell has the following advantages: (1) it can tolerate all single-node upset and partial double-node upset based on combining radiation hardened by polar design technology together with reasonable layout topology; (2) comparing with the state-of-the-art radiation hardened SRAM cells, simulation results show the proposed RHMC12T cell has lower write access time, higher wordline write trip voltage, larger static noise margin, and larger critical charge. And Monte Carlo simulation results have shown that RHMC12T has good robustness; (3) electrical quality metric is widely used to evaluate the overall performance of SRAM cells. And RHMC12T has the largest EQM compared with the state-of-the-art radiation hardened SRAM cells, which suggests the proposed RHMC12T exhibits good circuit performance (including write/read access time, static noise margin et al.) as well as good radiation resistance performance with sacrificing a large area overhead.